2016
DOI: 10.2215/cjn.00730116
|View full text |Cite
|
Sign up to set email alerts
|

High Density Lipoprotein Cholesterol and the Risk of All-Cause Mortality among U.S. Veterans

Abstract: Our results show a U-shaped relationship between HDL cholesterol and risk of all-cause mortality across all eGFR categories. The risk is modified by eGFR and cardiovascular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
138
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 172 publications
(150 citation statements)
references
References 25 publications
9
138
0
3
Order By: Relevance
“…The findings of the elegant study by Bowe et al (10) further strengthen the importance of evaluating HDL functionality and the limitations of relying solely on HDL-C levels for mortality risk prediction. Indeed, subjects with the highest HDL-C levels had increased all-cause mortality (10).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…The findings of the elegant study by Bowe et al (10) further strengthen the importance of evaluating HDL functionality and the limitations of relying solely on HDL-C levels for mortality risk prediction. Indeed, subjects with the highest HDL-C levels had increased all-cause mortality (10).…”
mentioning
confidence: 75%
“…In this context, the results of a recent study by Bowe et al are clinically relevant (10). In this study, a cohort of 1,764,986 US veterans were followed for a median of 9.1 years and the association between serum HDL-C levels and all-cause mortality was analyzed.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Taken together, these studies suggest that (I) the relationship between HDL-C and risk of death is not linear and; (II) HDL-C is a confounded measure and is a non-specific cardiovascular risk factor associated with noncardiovascular outcomes (6,7).…”
Section: Editorialmentioning
confidence: 94%
“…Recent Mendelian randomization analyses showed that genetic mechanisms that raise plasma HDL-C did not result in reduced risk of myocardial infarction (5). Given this background, recently Bowe et al took a big data approach to characterize the association between HDL-C and risk of death in a cohort of 1.7 million United States veterans followed for over 9 years and described-for the first time-a U-shaped association between HDL-C and risk of death in that both low and high HDL-C levels were associated with increased risk of death (6). In another study of 1.9 million United States veterans followed for 9 years, Bowe et al…”
Section: Introductionmentioning
confidence: 99%